Cognition, creativity, and behavior selected essays - Epstein, Robert (Praeger, 1996)
The volume paints a fairly consistent picture of Epstein's evolving view on cognition, creativity, and behavior. The first sections focus on generativity research and theory and on some "Columban" (pigeon) simulations of human behavior, including some related laboratory studies. The next sections cover efforts to create a comprehensive science of behavior; esssays about Skinner, one of the principal architects of behaviorism; and forays into artificial intelligence, child rearing, categorization research, and other topics. The volume concludes with some uncertain reflections on growing older and a modest proposal for a day of world peace
Keywords: Skinner, B. F <1904-1990> -- (Burrhus Frederic); Behaviorism; Behaviorism (Psychology); Cognition; Creative ability; Creativeness; Verhaltenswissenschaften; Behaviorismus; Verhalten; Kreativität; Kognition; Aufsatzsammlung